Italian guidelines for the prevention and management of dental trauma in children - Maria Grazia Cagetti; Piero Alessandro Marcoli; Mario Berengo; Piero Cascone; Livio Cordone; Patrizia Defabianis; Osvalda De Giglio; Nicola Esposito; Antonio Federici; Alberto Laino; Alessandra Majorana; Michele Nardone; et al. (BMC, 2019)
Abstract Dental trauma is a frequent occurrence in children and adolescent and a correct diagnosis and treatment are essential for a favourable long-term prognosis. The present Guidelines aim to formulate evidence-based recommendations to assist dentists, paediatricians, surgeons, teachers, school and sport staff, parents in the prevention and first aid of dental trauma in children and to provide a careful assessment of the medico-legal implications, reviewing the first draft of the guidelines published in 2012. A multidisciplinary panel on the behalf of the Italian Ministry of Health and in collaboration with the WHO Collaborating Centre for Epidemiology and Community Dentistry of Milan, developed this document. The following four queries were postulated: 1) Which kind of precautions the health personnel, parents, sports and educational personnel must activate in order to prevent the dental trauma damage? 2) How an orofacial trauma in paediatric patients should be managed either in the Emergency Care Unit and/or in private dental office? 3) What criteria should be adopted by a dentist private practitioner to fill in a certificate in cases of dental and/or tempomandibular joint trauma occurring in children and adolescents? 4) What are the elements that should lead clinicians to suspect a non-accidental dental trauma? A systematic review and analysis of the scientific literature published in English, Italian and French from 2007 to 2017 regarding dental trauma in children and adolescents aged 0-18 years was performed, and about 100 papers were analysed and included. The following four domains were analysed and discussed: Dental Trauma Prevention Strategies and Health Education, First aid in orofacial and dental trauma, Certificate of the dental trauma, Oral and dental signs of child abuse and neglect. Twenty-eight recommendations were draw up and codified by the panel according to the Methodological handbook, produced by the Istituto Superiore di Sanità, in order to guide physicians in the prevention and first aid of dental trauma in children and adolescents. In addition, a careful assessment of the medico-legal implications is reported in this document.